College Sophomore Students’ Self-Efficacy and Intent to Persist - Shelley Price-Williams; Pietro Sasso (Journal of College Orientation, Transition, and Retention)
This study centered on sophomore college students’ self-efficacy and intent to persist in higher education. Higher levels of self-efficacy were reported by participants who self-identified as heterosexual and on the Social Efficacy and Course Efficacy subscales. Further, the analyses revealed the distribution of scores in overall self-efficacy (p = .048) and social efficacy (p = .014) was lower among respondents who did not intend to return to higher education. These findings hold implications for the transformation of the first-year seminar, development of academic embedded seminars, and enhancement of academic and faculty relationships.